RESIDUAL LIFE PREDICTION AND CRACK GROWTH PROPERTY ANALYSIS FOR NO.17 GORGER COUPLER YOKE WITH SHALLOW SURFACE CRACK - JING ZhiMing; LIU YuJie; ZHANG Juan; KANG GuoZheng (Jixie qiangdu)
In view of the fact that most of the cracks in the coupler yoke are surface cracks with small depth and long length, the shallow surface crack propagation was simulated by FEA method for No.17 forged coupler yoke. The shape change of the surface crack was analyzed in the process of crack propagation, and the residual lives were predicted for the coupler yokes with different initial length and depth cracks. The results show that the shape of the elliptical surface crack of the coupler yoke changes and tends to be narrow and long during the propagation process. In the case of 0.5 mm and 1 mm initial crack depth, the residual lives of the coupler yokes were simulated for various crack lengths, and simulated results show that the forged coupler yoke has high anti-fracture resistance. For crack with the same initial length and depth, intermediate crack is more dangerous than corner crack. Based on the simulation results, a residual life prediction formula is obtained for the coupler yoke with the intermediate crack and corner crack under different initial crack lengths.